Accounting for Indicators of Budget Expenditure for Long-term Obligations Authorization - V. S. Anzhenko (Учёт. Анализ. Аудит, 2020)
Since the budget legislation changes every year, new federal standards are implemented, modern information technologies are introduced, accounting (budget accounting) in the public institutions is constantly developing. The article is devoted to the particularities of accounting for budget expenditure authorization (BEA) in these institutions as their both professional and economic activities have undergone certain changes. The methodological base of the study involves the approved normative legal acts and documents regulating accounting (budget accounting) for budget expenditure authorization. The research result is the development of an algorithm for the flow of limits of budgetary obligations (LBO) to account for and implement them when subsidies are granted for an extended period up to three years. The author provides recommendations on developing accounting policy on the example of public institutions of St. Petersburg for the year 2020. The results of the research could be of theoretical and practical interest for management and specialists of the public institutions in charge of keeping accounts and developing accounting policy.